An Evaluation of Grammar Settings in Textbooks—Take Junior High School English Textbooks Published by FLTRP for Example - Chenxiao Li (Journal of Advanced Research in Education, 2023)
Under the background of the new curriculum standard, grammar is still an important part of English basic education, which lays a solid foundation for the improvement of students’ core literacy. Many second language acquisition researchers have proposed that there is a relatively fixed natural route for second foreign language learners, but textbook editors and in-service teachers in China often ignore this sequence. Based on the natural order hypothesis and the input and output hypothesis, it is found in this thesis that English textbooks published by Foreign Language Teaching Research Press for junior high school students do not intend to follow the natural order but maintain a good balance in the design of grammar input-output activities.